2006
DOI: 10.2337/db05-1685
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Phospholipid Transfer Protein Activity Is Decreased in Type 2 Diabetes During Treatment With Atorvastatin

Abstract: Plasma phospholipid transfer protein (PLTP) plays an important role in lipoprotein metabolism. PLTP activity is elevated in patients with diabetes, a condition with strongly elevated risk for coronary heart disease. The aim of this study was to test the hypothesis that statins reduce PLTP activity and to examine the potential role of apolipoprotein E (apoE). PLTP activity and apoE were measured in patients with type 2 diabetes from the DALI (Diabetes Atorvastatin Lipid Intervention) Study, a 30-week randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…In a recent study in patients with type 2 diabetes, atorvastatin treatment resulted in a decrease in PLTP activity and an increase in PLTP mass, leading to a substantial change in mass-adjusted activity, which was related to apoE metabolism (37). In contrast, serum PLTP activity showed no significant changes in patients with type IIb hyperlipidemia after simvastatin treatment compared with controls (38).…”
Section: Discussionmentioning
confidence: 90%
“…In a recent study in patients with type 2 diabetes, atorvastatin treatment resulted in a decrease in PLTP activity and an increase in PLTP mass, leading to a substantial change in mass-adjusted activity, which was related to apoE metabolism (37). In contrast, serum PLTP activity showed no significant changes in patients with type IIb hyperlipidemia after simvastatin treatment compared with controls (38).…”
Section: Discussionmentioning
confidence: 90%
“…27 Plasma PLTP activity is expressed relative to control pool plasma. We measured HDL size by 4% to 30% nondenaturing polyacrylamide gradient gel electrophoresis as previously described.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…In type 2 diabetes, PLTP activity was positively correlated with plasma apoE levels. 18 Of the circulating PLTP mass only a minor portion is in the active form in normolipidemic subjects. 19 It has been reported that active PLTP in plasma is associated with apoE but not with apoA-I, 20 and apoE proteoliposomes can convert inactive PLTP into active one.…”
mentioning
confidence: 99%